Modelling of River Catfish (Cephalocassis Jatia) Population in Malaysia - Wan Saliha Wan Alwi; Muhamad Safiih Lola; Nur Edayu Zaini; Mohd Noor Afiq Ramlee; Abdul Aziz K Abdul Hamid (IAES Indonesian Section, 2022)
This research presents the mathematical modeling of the economic cycle of fish-population structures in Malaysia. This paper shows how to develop a model of river catfish based on system dynamics and simulates the model for policy planning and sustainable development. These experiences are essential if dynamic systems are to be modeled and simulated. The mathematical model predicts long-term trends for hatching, growth, and harvesting of the river catfish population. Simulated results suggest that the economic harvesting of adults entering the rivers has been discussed and effective strategies for sustainable fish production. Management strategies are put in place to harvest juvenile mortality and spawn adult harvesting, sustainable development of catfish could be maintained.